12 TEXTILE DYES DECOLORIZATION BY COPPER-RESISTANT-BACTERIA KLEBSIELLA GRIMONTII, SHIGELLA FLEXNERI, ENTEROBACTER CLOACAE ISOLATED FROM CISADANE RIVER TANGERANG - Wahyu Irawati; Vania Austine Callista Timotius; Ruben Patrick Adhiwijaya; Bellen Mouretta; Steven Anggawinata; Eunike Bunga Marvella (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Dyes and copper are dangerous contaminants because they are toxic. Bioremediation using indigenous bacteria is the best solution to overcome water pollution. Copper resistant bacteria usually have resistance to dyes thereby helping the bioremediation of dye and copper wastes. This study aims to examine the ability of indigenous bacteria isolated from the Cisadane River, namely Klebsiella grimontii IrCis3, Shigella flexneri IrCis5, Enterobacter cloacae IrCis6, and Enterobacter cloacae IrCis9 in terms of resistance and ability to decolorize 12 textile dyes namely methylene blue, malachite green, congo red, mordant orange, reactive black, direct yellow, basic fuchsin, reactive orange, dispersed orange, remasol red, wantex yellow and wantex red. The results showed that Shigella flexneri IrCis5, Enterobacter cloacae IrCis6, and Enterobacter cloacae IrCis9 were resistant to all dye concentrations of 200 and 500 ppm except Klebsiella grimontii IrCis3 did not grow on malachite green and basic fuchsin at concentrations of 200 ppm and methylene blue, malachite green and basic fuchsin concentration of 500 ppm. Only Shigella flexneri IrCis5 has the ability to decolorize 200 ppm basic fuchsin up to 87.23% after 3 days of incubation. The addition of 3 mM CuSO4 reduced the ability to decolorize Shigella flexneri IrCis5 to 0.57%.